RESULTS OF EXPECTANT WOMEN´S CARE WITH SEVERE PREECLAMPSY IN VILLA CLARA (2009-2010) - Juan Antonio Suárez González; Alexis Corrales Gutiérrez; María Rosa Cabrera Delgado; Mario Gutiérrez Machado; Isdekys Milián Espinosa; Juan Carlos Ojeda Blanco (Universidad de Ciencias Médicas de Villa Clara, 2013)
Introduction: Preeclampsia represents a risk for the mother and for the product of the conception. Objectives: To describe the results of the expectant women´s care with severe preeclampsia in Villa Clara during 2009 and 2010 years. Methods: A descriptive study of transversal type was carried out in 238 expectant women admitted at the special perinatal care´s ward of the Gynecological and Obstetric University Hospital "Mariana Grajales", who were diagnosed with severe preeclampsia between January, 2009 and December, 2010. Results: A number of 109 women (71,0 %), between 20 and 35 years old were diagnosed with severe preeclampsia. The average age was of 27, 3 years and nulliparity predominated (60,51 %). The 47,90 % of expectant women gave birth before the 37 weeks of pregnancy and the 43,27 % had newly born with a weight inferior to 2500 g; 15 of them weight less than 1000 grams (6,30 %).The were no considerable  maternal and perinatal complications. The main maternal complications were persistent hypertension during puerperium (13,02 %) and retroplacental hematoma (9,24 %); as well  as, main neonatal complications were low birth weight in 43,27 %, hypocalcaemia in 17,64 % and sepsis in 8,40 %. During this period there were not reported maternal deaths in the province. Conclusions: Severe preeclampsia care resulted in a minimum of maternal and perinatal complications and it was an important factor for the preservation of mother´s life with this suffering.